2020
DOI: 10.1155/2020/8833166
|View full text |Cite
|
Sign up to set email alerts
|

Exploring HIV-Related Stigma and Discrimination at the Workplace in Southwestern Uganda: Challenges and Solutions

Abstract: Globally, the HIV/AIDS pandemic continues to have an enormous impact on affected societies. Despite several health promotion interventions being carried out, HIV/AIDS remains a major cause of deaths in low and middle income countries. At the workplace, the pandemic has brought about reduction in productivity, increased staff turnover, increased production costs, high levels of stigma, etc. HIV stigma is one of the main reasons why the pandemic has continued to devastate a number of societies around the world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Our participants primarily framed pre-employment screening as a process which would enable employers to provide additional support to workers or for private health insurance schemes that would cover treatment. These narratives must be treated with caution, as despite formal national polices that prohibit discrimination (in the workplace) based on HIV status and that were referred to frequently by employers, evidence suggests that PLWHIV experience discrimination in the workplace, including being refused a work or employment opportunity, losing a job or source of income, and being refused promotion and/ or having their job description changed due to their HIV status [24,43,44]. Whilst the experience of HIV positive workers will undoubtedly vary across workplaces [45], for a clearer picture to emerge the voices of the HIV positive population (both employed and unemployed) need to be incorporated into the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants primarily framed pre-employment screening as a process which would enable employers to provide additional support to workers or for private health insurance schemes that would cover treatment. These narratives must be treated with caution, as despite formal national polices that prohibit discrimination (in the workplace) based on HIV status and that were referred to frequently by employers, evidence suggests that PLWHIV experience discrimination in the workplace, including being refused a work or employment opportunity, losing a job or source of income, and being refused promotion and/ or having their job description changed due to their HIV status [24,43,44]. Whilst the experience of HIV positive workers will undoubtedly vary across workplaces [45], for a clearer picture to emerge the voices of the HIV positive population (both employed and unemployed) need to be incorporated into the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in southwestern Uganda showed that stigma at the workplace remains a challenge to all people living with HIV, including expert clients. 25 To facilitate disclosure, PLWH normally undergo a series of counseling sessions by health workers and expert clients. PLWH felt stigmatized to disclose their HIV status.…”
Section: Experiences Of Expert Clients In Reducing Stigma and Discrim...mentioning
confidence: 99%
“…30 Expert clients were seen as a source of support for PLWH. 25 Expert clients would visit the homes of the nondisclosed PLWH to facilitate or encourage disclosure. 9 Furthermore, expert clients were able to draw on their own personal experience to support other women and their families, hence creating an approachable and rich source of advice concerning disclosure, psychological health, adherence, infant care, and navigating health services.…”
Section: Roles Of the Expert Clients In Reducing Stigma And Discrimin...mentioning
confidence: 99%
“…Healthcare providers may encounter HIV patients in various settings, in addition to the infectious disease sector; it is critical for them to deliver appropriate treatment to this population. However, evidence highlights most healthcare providers have low involvement in HIV prevention and care [ 3 ] and report stressors related to providing care for PLWHA [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%